2019
DOI: 10.2147/ceor.s203920
|View full text |Cite
|
Sign up to set email alerts
|

<p>Patient and economic burdens of postherpetic neuralgia in China</p>

Abstract: Background Little is known about the patient-reported and economic burdens of postherpetic neuralgia (PHN) among China’s urban population. Methods This noninterventional study was conducted among adults ≥40 years with PHN who were seeking medical care at eight urban hospitals in China. At one study site, patients completed a questionnaire evaluating the patient-reported disease burden (N=185). The questionnaire consisted of validated patient-reported outcomes including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 46 publications
(55 reference statements)
0
30
0
Order By: Relevance
“… 1 PHN is the most common complication of shingles, with an incidence of 5% to 30% in patients with herpes zoster. 2 It is a persistent, debilitating, and chronic pain condition that is characterized by spontaneous pain, hyperalgesia, allodynia, and paresthesia in the dermatomal areas where shingles was present. Patients consider these troublesome syndromes to be intolerable, and they interfere the sleep and cause depression, thereby decreasing a patient’s quality of life and leading to functional impairment and lost productivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 PHN is the most common complication of shingles, with an incidence of 5% to 30% in patients with herpes zoster. 2 It is a persistent, debilitating, and chronic pain condition that is characterized by spontaneous pain, hyperalgesia, allodynia, and paresthesia in the dermatomal areas where shingles was present. Patients consider these troublesome syndromes to be intolerable, and they interfere the sleep and cause depression, thereby decreasing a patient’s quality of life and leading to functional impairment and lost productivity.…”
Section: Introductionmentioning
confidence: 99%
“… 3 PHN causes an increase in the use of health care resources and an increased economic burden on society. 2 , 4 …”
Section: Introductionmentioning
confidence: 99%
“…The study found total direct medical costs of ¥10,600. The costs were driven by higher hospitalization costs of ¥9300 compared to our study, which was driven mostly by higher drug costs [16]. The societal costs of patients with rheumatoid arthritis across 21 tertiary care hospitals between July 2009 and December 2010 were studied [17].…”
Section: Discussionmentioning
confidence: 66%
“…Resource utilization included physician visits of 9.33 per year and 0.23 hospital days per year (physician survey). The cost per physician visit (¥298.72) and hospital day (¥841.90) was sourced from a recent burden of illness study for postherpetic neuralgia in China [16]. A cost per year for lab tests (¥508.33) and radiologic tests (¥808.33) was also applied to patients.…”
Section: Model Inputsmentioning
confidence: 99%
“…Among those cases, 30% [2] are predicted to develop PHN after 12 weeks. Recent investigation [4] has shown that PHN is associated with sleep disturbances, lower quality of life, restricted daily activities and increased medical costs, all of which impose heavy burden on the patient and their finances. In addition, neuropathic pain [5] often persists for months or years and is refractory to drugs.…”
Section: Background and Rationale {6a}mentioning
confidence: 99%